Meningkatkan Aktivitas Dan Hasil Belajar Siswa Menggunakan Model Flashback Di SDN Sungai Miai 8 - Chusnul Islamiah; Sulaiman Sulaiman (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The problems experienced in this study were the low activity and learning outcomes of students due to the learning still memorized the material, lack of student interest, students were less involved and students did not work together in groups. To overcome these problems researchers use the Flashback model in the learning process. This study aims to describe student activity, teacher activity, and student learning outcomes. The research uses a qualitative approach with the type of Classroom Action Research (CAR), which is carried out in 4 meetings. The research subjects were fourth grade students at SDN Sungai Miai 8 Banjarmasin with a total of 24 students. Data analysis used descriptive analytical techniques presented in the table. The results of research in meeting I - IV show (1) Teacher activity achieves a score of 34 in the very good category. (2) Student activity reaches a percentage of 96%. (3) Student learning outcomes achieve 96% classical completeness.